2014
DOI: 10.1002/asl2.516
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting Madden–Julian Oscillation activity during various stages of EP and CP El Niños

Abstract: This study revisits the relations between Madden-Julian Oscillation (MJO) and El Niño that is classified as eastern Pacific (EP) and central Pacific (CP) types. During an EP-type event that produces lasting dry conditions in the Maritime Continent and western Pacific, the MJO activity is weak especially in its 4th-6th phases as a strong response. In contrast during CP-type episodes, the MJO exhibits notably enhanced and suppressed amplitudes in its different phases. The low-level westerly wind anomalies of enh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 27 publications
2
23
0
Order By: Relevance
“…During El Niño, the western subsiding branch of the Walker circulation moving westward leads to the suppressed convection and moisture flux convergence over the MC. Weakened seasonal‐mean moisture over the MC prevents the BSISO initiated from the Indian Ocean from passing the MC during the summer monsoon season (Lin and Li, ; Liu, Li, Wang, Deng, & Zhang, ; Teng & Wang, ) and reduces the intensity of the MJO through the feedback effect of convective heating (Chen, Ling, & Li, ; Feng, Liu, Chen, & Wang, ). The opposite occurs during La Niña.…”
Section: Resultsmentioning
confidence: 99%
“…During El Niño, the western subsiding branch of the Walker circulation moving westward leads to the suppressed convection and moisture flux convergence over the MC. Weakened seasonal‐mean moisture over the MC prevents the BSISO initiated from the Indian Ocean from passing the MC during the summer monsoon season (Lin and Li, ; Liu, Li, Wang, Deng, & Zhang, ; Teng & Wang, ) and reduces the intensity of the MJO through the feedback effect of convective heating (Chen, Ling, & Li, ; Feng, Liu, Chen, & Wang, ). The opposite occurs during La Niña.…”
Section: Resultsmentioning
confidence: 99%
“…They also showed that this shift is linked with ENSO. Feng et al [] found different MJO activities during various stages of the eastern Pacific and central Pacific El Niño. It is likely that the lack of relationship between PC1 and ENSO in the present study is due to the fact that the RMM index is designed to remove the ENSO signal.…”
Section: Interannual Variability Of the Mjomentioning
confidence: 99%
“…In addition, a possible connection to the El Niño/Southern Oscillation (ENSO; Figure c), a dominant source of interannual variability in the tropical troposphere and the ocean, has previously been explored [ Hendon et al ., ; Slingo et al ., ; Hendon et al ., ]. Despite some reports of MJO activity changes during different ENSO phases [ Gushchina and Dewitte , ; Feng et al ., ], an ENSO‐MJO link is still not well established [ Lin et al ., ]. Apart from an association with sudden stratospheric warming [ Garfinkel et al ., ; Liu et al ., ; Albers et al ., ], there has been little work linking the MJO to stratospheric variability, especially to the QBO [ Liu et al ., ].…”
Section: Introductionmentioning
confidence: 99%